SECURE DATA STORAGE USING THE ETHEREUM BLOCKCHAIN TECHNOLOGY - Harasymchuk , Oleh; Nakonechnyi , Yurii; Lukovskyy , Taras; Andriiv , Roman; Nakonechnyi , Taras (Ukrainian Information Security Research Journal, 2024)
The constant increase in the amount of data creates problems related to the choice of effective methods and means of storage and ensuring the protection of this data from unauthorized access. The article details the critical topic of preserving and protecting the importance of information in the context of growing data volumes and the number of cyberattacks. The impossibility of reliable data storage and protection is increasing, especially in the context of the increased threat from attackers. It highlights how blockchain technologies, especially based on the Ethereum platform, can solve the problems of reliable storage and data security. Ethereum offers an alternative to the traditional client-server model by decentralizing data storage through a distributed network of nodes. This technology significantly improves security, making unauthorized access to information difficult, and preventing the hacking of the private key, which requires significant computing resources. Smart contracts on Ethereum allow the creation of applications that execute precisely according to predetermined conditions, without the possibility of third-party intervention. This is especially important for messengers, where data privacy and availability are of fundamental importance. Although high, the cost of transactions in the blockchain is compensated by the high reliability and security of data storage. The applied methodology confirms that public (decentralized) data storage is safe since it is practically impossible to break the private key of Ethereum.